Kemasan Tari Kejai Dalam Pesta Perkawinan Di Desa Tunggang Kecamatan Lebong Utara Kabupaten Lebong Provinsi Bengkulu - Ririz Dwi Oktaviani; Desfiarni Desfiarni (FBS Universitas Negeri Padang, 2021)
This study aims to identify and describe the packaging of the Kejai Dance in a Wedding Party in North Lebong Village, Bengkulu Province. This type of research is a qualitative research with descriptive method. The instruments in this study were the researchers themselves and were assisted by supporting instruments such as stationery, cameras, cellphones and flash drives. This type of data uses primary data and secondary data. Data collection techniques were carried out by means of library research, observation, interviews and documentation. The stages of data analysis are data collection, data reduction, data presentation and drawing conclusions. The results show that the new Kejai Dance is a modification of the old Kejai Dance which still remains the identity of the Kejai Dance (local culture of the Rejang Region). The new packaging forms for the modified Kejai Dance include: 1) movement; 2) floor pattern; 3) dancers; 4) music; 5) costumes; 6) property; and 7) duration of appearance